A formação profissional em serviço social e questão ético-política no contexto da expansão do ensino superior no Maranhão - SOUZA, Camila Cristina de Castro (2019)
Study on the professional formation in Social Work and the ethical-political question in the context of the expansion of higher education, in the particularity of Maranhão, based on a survey and analysis of official data of the Ministry of Education and political-pedagogical projects of courses of Social Service in the state. According to the trans-formations orchestrated by capitalism under neoliberalism, the educational reform of higher education, as an education project, was expressed in an expansion of private education and the modality of distance learning mainly for baccalaureate students. As part of a global strategy, international organizations guide dependent economy coun-tries to professional training that is functional to the interests of capital expansion with-out commitment to the formation of critical thinking, based on "aulism" that favors teaching, dissociated from research and of the extension. In order to understand this process and its impact on professional training in Social Work, a bibliographical and documentary theoretical study was undertaken, attempting to rescue the elements of ethical-political construction required by Social Work and its correspondence in profes-sional training, at the same time as the Institutions of Higher Education of different modalities are analyzed, in order to unveil the conceptions and political-pedagogical projects proposed for the courses of Social Service in Maranhão. The results are pre-sented in two chapters. The first points to historical and theoretical grounds for thinking about the ethical-political question and the professional training in Social Work. The second makes a reflection on education and training process pointing trends on the expansion of teaching and vocational training in Social Work in higher education in Maranhão.